PENGARUH LOKASI DAN FASILITAS TERHADAP KEPUASAN PENGHUNI PERUMAHAN AMORA LAND PROPERTY SINTANG - Asrori, Imam; Adhita Octaviani, Venny (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2024)
This research was conducted to analyze the influence of location and facilities on the satisfaction of residents of Amora Land Property Sintang housing with a sample of 54 consumers who had purchased housing at Amora Land Property Sintang. The results of the research partially show that location has a significant effect on consumer satisfaction (sig t count > 0.05). Furthermore, facilities have a significant effect on consumer satisfaction (sig t <0.05). The results of the F test showed that location and facilities together (simultaneously) influenced the satisfaction of residents of the Amora Land Property Sintang housing complex as indicated by the calculated F significance value <0.05.